Applicability of satellite radar imaging to monitor the conditions of levees. (28th November 2018) - Özer, Işıl E.; van Leijen, Freek J.; Jonkman, Sebastiaan N.; Hanssen, Ramon F.
Abstract : Levees are critical systems in safeguarding an area against catastrophic flooding events with potential fatalities and economic losses. Current monitoring methods of levees highly rely on expert judgement, resulting in infrequent and subjective assessments of their status. Satellite radar imaging, in particular using interferometry (InSAR), holds a large potential to monitor the condition of levees with millimetre‐level precision, anywhere on the planet. However, for levee management, the usability of the technique requires significant radar expert knowledge. Here, we provide a comprehensive overview of the state of the art in using time‐series InSAR for systematic levee deformation monitoring. We explore its use to complement existing approaches for assessing levee deformation and failure investigations in a fast, systematic, and cost‐effective way. The applicability of imaging radar satellites is discussed, supported by case studies on levee monitoring in the Netherlands. We elaborate on the technical aspects with respect to levee monitoring using SAR technology, such as estimating deformation in different directions, satellite characteristics, precision, and reliability. We conclude that InSAR is becoming an operational deformation monitoring system, which allows for the detection, tracking, and analysis of irregularities on levee sections with increased efficiency and quality, thus contributing to improved risk management.